(untitled) (Studia austriaca, 2016)
Numerous readers of Celan, among them Giuseppe Bevilacqua and John Felstiner, have pointed out diverse references to death by drowning. This biographical paper picks up evidence systematically and chronologically, thereby rejecting any «special attraction» to the element of water. By focussing Celan’s poem Kenotaph, we can see a clear connection to the «Goll affair». Only in 1967, when the poem Brunnengräber was written, plans for death by drowning became apparent. Such plans further developed in renditions of Dupin and Rokeah. Gisèle Celan-Lestrange’s graphic Les flots se fermant also deals with this issue. Celan’s personal statements before his death reveal a strong interest in Hölderlin.